2019
DOI: 10.3390/ijerph17010093
|View full text |Cite
|
Sign up to set email alerts
|

Youth Engaged Participatory Air Monitoring: A ‘Day in the Life’ in Urban Environmental Justice Communities

Abstract: Air pollution in Southern California does not impact all communities equally; communities of color are disproportionately burdened by poor air quality and more likely to live near industrial facilities and freeways. Government regulatory monitors do not have the spatial resolution to provide air quality information at the neighborhood or personal scale. We describe the A Day in the Life program, an approach to participatory air monitoring that engages youth in collecting data that they can then analyze and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 59 publications
1
43
0
Order By: Relevance
“…Similarly, local-scale air quality studies have identified a gap in, and the need for, high resolution data for both pollutant concentrations and baseline disease rates to identify intra-city inequities in attributable health risks (Castillo et al, 2021;Southerland et al, 2021). This high-resolution data also helps engage communities, as well as understand local exposure to pollutants, pollution sources, and vulnerability to exposure (e.g., Johnston et al, 2019), while it helps ensure continued community involvement and health improvements even after funding and studies are finalized (English et al, 2017). Although air quality has been extensively studied globally, systematic reviews and meta-analyses for physical activity, green space, and noise exposures are supported by fewer studies.…”
Section: Future Research Needsmentioning
confidence: 99%
“…Similarly, local-scale air quality studies have identified a gap in, and the need for, high resolution data for both pollutant concentrations and baseline disease rates to identify intra-city inequities in attributable health risks (Castillo et al, 2021;Southerland et al, 2021). This high-resolution data also helps engage communities, as well as understand local exposure to pollutants, pollution sources, and vulnerability to exposure (e.g., Johnston et al, 2019), while it helps ensure continued community involvement and health improvements even after funding and studies are finalized (English et al, 2017). Although air quality has been extensively studied globally, systematic reviews and meta-analyses for physical activity, green space, and noise exposures are supported by fewer studies.…”
Section: Future Research Needsmentioning
confidence: 99%
“…It allows easy and stable communication between NGSMs and a smartphone in which the mobile app is supported. In this review, 23 articles [ 19 , 27 , 32 , 35 , 37 , 38 , 39 , 50 , 51 , 56 , 60 , 67 , 69 , 77 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ] out of 67 reports information about the use of any mobile app supporting NGMSs; most of those (13 apps) were developed on the Android platform [ 6 , 35 , 37 , 38 , 40 , 50 , 53 , 60 , 81 , 84 , 86 , 87 , 88 ], only one was developed on the iOS platform [ 81 ], and the remaining were not specified. As reported by Kanjo et al [ 89 ], using a mobile phone to collect data can bring many advantages, especially related to the fact that (i) a large percentage of the population carries around mobile phones; (ii) many kinds of data can be processed, stored, and transferred easily by mobile phones; (iii) the collection of data should be more power-efficient because the acquired information are sent directly to the mobile phone.…”
Section: Resultsmentioning
confidence: 99%
“…Across California, people of colour are more likely to live near facilities that emit fine particulate matter (particles <2.5 μ in diameter, PM 2.5 ), a pollutant which increases the risk of cardiovascular disease, respiratory disease, and neurological disorders. Johnston et al ( 2019 ) note that, by providing youth participants with portable personal PM 2.5 monitors, citizen science can ‘build upon principles of community-driven participatory research, which seeks to deconstruct traditional power dynamics, provide information about environmental hazards important to residents, and democratise knowledge’. This democratisation of knowledge exemplifies how citizen scientists collecting health-related pollution data can address environmental injustice.…”
Section: The Current Landscapementioning
confidence: 99%